3(x-1)+5x=24

Simple and best practice solution for 3(x-1)+5x=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)+5x=24 equation:


Simplifying
3(x + -1) + 5x = 24

Reorder the terms:
3(-1 + x) + 5x = 24
(-1 * 3 + x * 3) + 5x = 24
(-3 + 3x) + 5x = 24

Combine like terms: 3x + 5x = 8x
-3 + 8x = 24

Solving
-3 + 8x = 24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 8x = 24 + 3

Combine like terms: -3 + 3 = 0
0 + 8x = 24 + 3
8x = 24 + 3

Combine like terms: 24 + 3 = 27
8x = 27

Divide each side by '8'.
x = 3.375

Simplifying
x = 3.375

See similar equations:

| 2.50x+3.50y=132 | | N+3.5=6.5 | | 2x+1=5x+13 | | E=2H-13 | | 10x-65=6x+50 | | B=h(b+c) | | 6n^2-12n-39=9 | | E+H=23 | | b=(a+c) | | 0.02-0.3=x | | 2(3x-4)-7x+2=-15 | | 6x-12=4x-5 | | 9/10t=9 | | 4x+5x+3x=100 | | 2y+7(2y+20)=20 | | 3x^4+11x^3-40x^2-132x+48=0 | | 5+6x(x+2)=5y+8 | | F(0)=-x^2-6x+9 | | 6x^2=x^2+125 | | 3x^4+11x-40x^2-132x+48=0 | | 9-3(x+4)=12-6(x-1) | | 5=8/4 | | 7y+5=14 | | X^2-7x-408=0 | | 17ln(x)=20 | | 22x-2x=60 | | 17lnx=20 | | X/(-3)=-5 | | -a^2+7a+4= | | 6(x+2)-6=24 | | .1725= | | 12x+-14=76+9x |

Equations solver categories